Statistical design of sustainable composites from poly(lactic acid) and grape pomace. Issue 36 (8th March 2020) - Gowman, Alison; Rodriguez‐Uribe, Arturo; Defersha, Fantahun; Mohanty, Amar K.; Misra, Manjusri
Abstract: Biocomposites from poly(lactic acid) (PLA) and grape pomace (GP) were created via injection molding to examine the effects of GP in a PLA matrix. To optimize the mechanical performance the biocomposites were compatibilized with maleic anhydride grafted PLA (MA‐ g ‐PLA). The objective of this work was to create a model that could accurately predict the mechanical properties of GP/PLA biocomposites. A region of feasibility for the biocomposites was determined using a statistical design of experiments. Linear regression was used to model the mechanical performance and predicted results with an error of 10% for both tensile and flexural strength and 16% for impact strength. The model was verified with a biocomposite of PLA/GP/MA‐ g ‐PLA with a ratio of 62/36/2. This biocomposite had a tensile strength, flexural modulus, and impact strength of 25.8 MPa, 40.0 MPa, and 18.4 J/m, respectively. It was found that a linear model can accurately predict the mechanical properties of PLA/GP/MA‐ g ‐PLA biocomposites. Abstract :